2010
DOI: 10.1186/1743-0003-7-39
|View full text |Cite
|
Sign up to set email alerts
|

Assessing motor deficits in compressive neuropathy using quantitative electromyography

Abstract: BackgroundStudying the changes that occur in motor unit potential trains (MUPTs) may provide insight into the extent of motor unit loss and neural re-organization resulting from nerve compression injury. The purpose of this study was to determine the feasibility of using decomposition-based quantitative electromyography (DQEMG) to study the pathophysiological changes associated with compression neuropathy.MethodsThe model used to examine compression neuropathy was carpal tunnel syndrome (CTS) due to its high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…On contrary this, we found that CMAP Amplitude was not decreased only in patients with severe CTS as a result of the loss of motor units but also in mild CTS. Unlikely our finding, Nashed et al found that there was no difference in peak-to-peak MUAP amplitude between the mild CTS and the control groups [20]. It can be result in due to their very small study group (nine control group and eight mild CTS) In many previous studies, CMAP NP full-duration prolongation assessed by measuring NP is commonly used in CIDP as diagnostic parameter [21][22][23][24][25].…”
Section: Discussioncontrasting
confidence: 90%
“…On contrary this, we found that CMAP Amplitude was not decreased only in patients with severe CTS as a result of the loss of motor units but also in mild CTS. Unlikely our finding, Nashed et al found that there was no difference in peak-to-peak MUAP amplitude between the mild CTS and the control groups [20]. It can be result in due to their very small study group (nine control group and eight mild CTS) In many previous studies, CMAP NP full-duration prolongation assessed by measuring NP is commonly used in CIDP as diagnostic parameter [21][22][23][24][25].…”
Section: Discussioncontrasting
confidence: 90%
“…MUNE has been applied to compression neuropathies and postpolio syndrome and has shown correlations with disease severity [110,111].…”
Section: Mune In Other Neuromuscular Diseases and Normal Agingmentioning
confidence: 99%
“…2 In an assessment of motor deficits in nine healthy participants, eight patients with mild, and six individuals with severe CTS, no differences in the median age or sex among the groups were found. 19 However, the small sample size may be an indication that those studies were inadequately powered to detect clinically important effects. Also, our sample had higher mean age and higher mean time since injury.…”
Section: 24-718-21mentioning
confidence: 99%
“…2 While some others found associations in terms of duration of symptoms. 1,4,19 Previous studies included different sample sizes from 23 patients 19 to 126 participants 4 and therefore had considerable uncertainty around the prevalence of CTS in long-term wheelchair users, reflected in the wide range of the estimates. Therefore, to estimate the prevalence of CTS and to assess the impact of using wheelchair over the long term in paraplegic patients a large study is still required.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation